2013
DOI: 10.15446/ing.investig.v33n3.41035
|View full text |Cite
|
Sign up to set email alerts
|

The influence of adding corrosion inhibitor and pH on the electrochemical properties of hybrid films applied to galvanised steel

Abstract: This study was aimed at coating galvanised steel with a hybrid film obtained from a sol consisting of silane precursors 3 - (trimetoxisililpropil) methacrylate (TMSPMA) and tetraethoxysilane (TEOS). The pH of the hydrolysed-silane solution was 1 and 3. The influence of adding corrosion inhibitor (i.e. 0.01M cerium nitrate) was evaluated for all samples. The hybrid films were deposited by dip-coating. The film was characterised scanning electron microscopy (SEM), profilometry, contact angle measurement, potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results were reached in (site -2) within close limits to the previous time period after making a change in the injection site of the neutralizing amine, which is suggested by the research, as it will be, as we mentioned in the body of the research, in the return site from the stripper tower towards the main tower and as shown in the Figure (6) We will study the results and the differences through the results of Table (2).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The results were reached in (site -2) within close limits to the previous time period after making a change in the injection site of the neutralizing amine, which is suggested by the research, as it will be, as we mentioned in the body of the research, in the return site from the stripper tower towards the main tower and as shown in the Figure (6) We will study the results and the differences through the results of Table (2).…”
Section: Resultssupporting
confidence: 68%
“…Studies show that dissolved salts and hydrochloric acid form different forms of corrosion in distillation tower metal, depending on the temperature gradient (boiling point values) and concentration. The wear of the oil and gas production tray area differs from that of Tray 24 and tray 28 as shown in Figure (2). Table ( 1) Also shows the areas and the cause of corrosion for each area.…”
Section: Fig (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in environments containing bacteria, the corrosion behavior of materials may be different at different environmental conditions. Nevertheless, the recent literature focused mostly on the MIC behavior of galvanized steel at a neutral pH (pH 7) [11,12]. Several previous studies show that some Pseudomonas species activities are inhibited at pH below 7 while some others have the ability to grow well even in a very low pH environment [11].…”
Section: Introductionmentioning
confidence: 99%